Hypoxia-inducible factor-1α promotes endometrial stromal cells migration and invasion by upregulating autophagy in endometriosis. Issue 6 (June 2017) - Liu, Hengwei; Zhang, Zhibing; Xiong, Wenqian; Zhang, Ling; Xiong, Yao; Li, Na; He, Haitang; Du, Yu; Liu, Yi
Abstract : Endometriosis is a benign gynecological disease that shares some characteristics with malignancy like migration and invasion. It has been reported that both hypoxia-inducible factor-1α (HIF-1α) and autophagy were upregulated in ectopic endometrium of patients with ovarian endometriosis. However, the crosstalk between HIF-1α and autophagy in the pathogenesis of endometriosis remains to be clarified. Accordingly, we investigated whether autophagy was regulated by HIF-1α, as well as whether the effect of HIF-1α on cell migration and invasion is mediated through autophagy upregulation. Here, we found that ectopic endometrium from patients with endometriosis highly expressed HIF-1α and autophagy-related protein LC3. In cultured human endometrial stromal cells (HESCs), autophagy was induced by hypoxia in a time-dependent manner and autophagy activation was dependent on HIF-1α. In addition, migration and invasion ability of HESCs were enhanced by hypoxia treatment, whereas knockdown of HIF-1α attenuated this effect. Furthermore, inhibiting autophagy with specific inhibitors and Beclin1 siRNA attenuated hypoxia triggered migration and invasion of HESCs. Taken together, these results suggest that HIF-1α promotes HESCs invasion and metastasis by upregulating autophagy. Thus, autophagy may be involved in the pathogenesis of endometriosis and inhibition of autophagy might be a novel therapeutic approach to the treatment of endometriosis.